Effect of Perceptions of Professional Image on the Profession Preferences of Nursing Students: A Multi-Centered Study - Totur Dikmen, Burcu (2022)
Stepping into the nursing profession, staying in the profession and career development in the profession are stated to be the result of perceptions of nurses about the image of the profession. The study aims to determine the effect of perceptions of the professional image of nursing students on their profession preferences. The descriptive study was conducted in nursing departments of six universities in Turkey and Cyprus. The sample consisted of 874 freshman students who voluntarily agreed to participate in the research. The data were collected using the introductory information form and the "Image of Nursing Profession Scale". The average score of the nursing students on the Image of Nursing Profession Scale was 152.2 ± 11.4. A statistically significant difference was found in the Image of Nursing Profession Scale total score average in terms of the gender, undergraduate program, choosing the nursing profession willingly, consideration the image of the profession when choosing the nursing profession variables ( p <.05). The nursing students were found to have a good level of perceptions of professional image towards the nursing profession. Individual characteristics and the economic situation of the profession were found to positively affect the voluntary choice of the nursing profession.